Patient-Reported Outcomes in Rheumatoid Arthritis: Why are They Important and How Should They Be Assessed? - Laure Gossec, (Archives of Rheumatology, 2010)
Patient reported outcomes have become increasingly important in the evaluation of rheumatoid arthritis (RA) over recent years. Besides pain and functional capacity, fatigue, sleep and wellbeing are also important for RA patients. We will discuss here the importance of patient-reported outcomes, different domains of health, and how to evaluate them, with a focus on questionnaires available in Turkey. (Turk J Rheumatol 2010; 25: 99-104)